Eksistensi Hukum Waris Adat Patrilineal Di Kabupaten Sikka Provinsi Nusa Tenggara Timur - Osa, Agustina Dua; Nuwa, Gustav Gisela; Kasim, Abdul Muis (Jurnal Kepastian Hukum dan Keadilan, 2022)
This study aims to determine the implementation of customary inheritance law and the process of settlement of inheritance disputes based on customary inheritance law applicable in Sikka Regency. This study uses a qualitative approach with measuring instruments for data collection using structured, semi-structured, and observational interviews. The sampling technique used in this research is snowball sampling. The source of the data used is primary data from interviews with 10 informants who are elders and administrators of village traditional institutions in several villages in Sikka district. The results of this study reveal that the description or condition of the implementation of customary inheritance law in the patrilineal kinship system in Sikka Regency in the distribution of land inheritance is given full power to sons so that the amount of distribution is different from that of girls, while the dispute resolution process is based on negotiations after there is no settlement, then by means of deliberation to reconcile the disputing parties by the Village Customary Institution and the Village Government.Keywords: The Existence of Customary Inheritance; Customary Inheritance Law; Patrilineal System